Lifetime semen production performance of cattle and buffalo bulls - K. G. Bhave; K.Thilak Pon Jawahar; P.Kumarasamy; T. Sivakumar; Cecelia Joseph; S. Sontakke; J. Khadse; R. Venkataramanan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Semen production performance data of 88 buffalo and 179 cattle bulls of different breeds from 1975 to 2018, were collected from two frozen semen stations of BAIF Research Development Foundation. The objective of the present study was to document the lifetime semen producing performance of cattle and buffalo bulls. Traits studied were lifetime frozen semen production doses (LFSP),lifetime production period (LPP),age at first semen production (AFSP) and age at last semen production (ALSP). The factors tested for influence on these traits were breed, period and season of birth. Overall means of AFSP, ALSP, LPP and LFSP were 1859.6, 4257.2, 2581.7 days and 183631.9 semen doses in buffalo bulls, while 1386.7, 4029.4, 2076.16 days and 264566.3 semen doses in cattle bulls. Production performance for results obtained for various breeds could be useful in devising important culling and disposal policies for AI centres in the country.